Development of a multiplex fluorescent immunoassay for the simultaneous detection of serum antibodies to multiple swine pathogens - Wang, Yu (Kansas State University, 2013)
Three economically important swine diseases: Porcine Reproductive and Respiratory Syndrome (PRRS), Porcine Circovirus Associated Disease (PCVAD) and Swine influenza cost the US swine industry more than a billion dollars each year. This study developed a fluorescent microsphere immunoassay (FMIA) to simultaneously detect antibodies to the causative pathogens: PRRSV, porcine circovirus (PCV2) and swine influenza virus (SIV). The results showed that the multiplex assay possessed the predicted specificities. In the case of PRRSV NA, the assay displayed higher sensitivity when compared to a commercially available ELISA. The assay was employed to measure both IgG and IgM responses. The FMIA was found to possess several advantages over standard ELISA which include reduced sample volume, time and cost and provides a new tool for veterinary diagnostics. The FMIA was applied for swine disease surveillance in Hawaiian and Texan feral swine populations. The antibodies against PCV2 showed the highest prevalence among these three pathogens in both Hawaii and Texas. Hence we consider PCV2 as the most prevalent pathogen in Hawaiian and Texan feral pigs and this pathogen poses the greatest threat to commercial pigs. SIV seroprevelance increased from 2007 to 2010 in Hawaii State, suggesting an increasing risk for commercial pigs. Moreover, yearly surveillance in Texas State shows growth in seropositive response to all pathogens, particularly PCV2. The development of FMIA for detection of antibodies to multiple swine pathogens in serum samples offers an important alternative for swine disease surveillance in commercial and feral herds.
Keywords: Swine pathogens; Immunoassay; Luminex; Veterinary Medicine (0778)